Sustainability of foreign trade deficit in energy: The case of Turkey - (:unkn) unknown (IGI Global, 2016)
The sustainability of foreign trade deficit in energy becomes even more important for those countries that do not have sufficient energy resources and that have to import energy. As long as the countries' dependency on imported energy resources continues, the size of the foreign trade deficit in energy will have a direct impact on the sustainability of the current accounts deficit. Although there are numerous studies that examine empirically the countries' current accounts deficit and the sustainability of foreign trade deficit in literature through different unit root tests, no studies have been found that examine the sustainability of foreign trade deficit in energy. For this reason, the sustainability of foreign trade deficit in energy in Turkey between 1969-2013 was examined using the linear and non-linear unit root tests. The findings showed that Turkey's foreign trade deficit in energy is not sustainable. Having obtained such an outcome based on empirical findings is of paramount importance with respect to Turkey's long term growth and security projections. © 2017 by IGI Global.